Evaluation of movement programmes in the treatment of dyslexia - Doyle, Erika (Trinity College (Dublin, Ireland). School of Psychology, 2008)
Developmental dyslexia, or specific learning difficulty, is a prevalent condition, affecting up to 10% of the population, which can be severely disabling without early diagnosis and persistent and intensive remediation. This study evaluates claims that the condition is linked to the abnormal persistence of early motor reflexes in the child’s profile or to a deficit in cerebellar function and that the condition can be remediated by either a programme of replicating primary reflex movements or a programme designed to enhance control of balance.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin